Kesehatan Kerja Sebagai Hak Asasi: Analisis Hukum Atas Perlindungan Tenaga Kerja dan BPJS Ketenagakerjaan - Fathi Rahmah Safira (Jurnal JURISTIC, 2026)
This study examines occupational health law, focusing on legal protection for workers against occupational accidents and work-related diseases, the implementation of occupational health regulations in high-risk industrial sectors, and the role of BPJS Ketenagakerjaan in ensuring workers' health protection. Employing a normative juridical research method, the study analyzes national and international legal frameworks, theories of legal protection, and their practical implementation. The findings reveal that although the legal framework governing occupational health is relatively comprehensive, its implementation continues to face significant challenges, including weak corporate compliance, limited regulatory oversight, and low levels of legal awareness among workers. Furthermore, while BPJS Ketenagakerjaan plays a crucial role in providing social security and occupational health protection, its effectiveness is constrained by bureaucratic procedures, delays in benefit disbursement, and limited coverage of informal sector workers. Therefore, strengthening the legal framework, enhancing regulatory enforcement, and expanding access to social security programs are essential to ensure that occupational health law effectively provides comprehensive legal protection for the workforce.